THE RESTORATION OF PERIKLES’ ODEION AT ATHENS IN THE FIRST CENTURY BC: NEW AND ANCIENT BARBARIANS (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2016)
This paper discusses the restoration project of the Odeion of Perikles at Athens, carried by the Cappadocian king Ariobarzanes II sometime between 63 and 52 BC, after its partial destruction during the Sullan sack of 86 BC. This sack occurred as a punishment for the alliance between Athens and the Pontic king Mithridates VI in his war against Rome. In that context, the restoration project of this fifth century B.C. covered-theatre was meaningful for the formation of diplomatic links and networks between Athens, Rome and Cappadocia, in particular considering the complexity of the antibarbarian narratives involved. From the viewpoint of the Athenian urban history, the restoration project is an eloquent example of a new attitude towards the urban space which would become a central feature in the social production of Athenian space throughout the first century B.C.: the antiquarian urbanism.